Technical Review: Cytogenetic Tools for Studying Mitotic Chromosomes - Bačovský, Václaclav; Hobza, Roman; Vyskot, Boris (Methods in molecular biology (Clifton, N.J.), 2018)
Significant advances in chromosome preparation and other techniques have greatly increased the potential of plant cytogenetics in recent years. Increase in longitudinal resolution using DNA extended fibers as well as new developments in imaging and signal amplification technologies have enhanced the ability of FISH to detect small gene targets. The combination of fluorescence in situ hybridization with immunocytochemistry allows the investigation of cell events, chromosomal rearrangements and chromatin features typical for plant nuclei. Chromosome manipulation techniques using microdissection and flow sorting have accelerated the analysis of complex plant genomes. Together, the different cytogenetic approaches are invaluable for the unravelling of detailed structures of plant chromosomes, which are of utmost importance for the study of genome properties, DNA replication and gene regulation. In this technical review, different cytogenetic approaches are discussed for the analysis of plant chromosomes, with a focus on mitotic chromosomes.
Keywords: Plants; Cytogenetics; hybridizace in situ fluorescenční; restrukturace chromatinu; Mitosis; Cell synchronization; imunohistochemie; chromozomy rostlin; Chromosomes, Plant; rostliny; FISH; Antibodies; Immunohistochemistry; Laser microdissection; Immunostaining; In Situ Hybridization, Fluorescence; mitóza; Chromosome spreads; cytogenetické vyšetření; Chromatin Assembly and Disassembly; Cytogenetic Analysis